Potencial and Strategic Development of Peri-Urban Agriculture in Bogor District - Andriamasari, Herwita; Mugnisjah, Wahju Qamara; Munandar, Aris (Jurnal Ilmu Tanah dan Lingkungan, 2015)
There is a growing newtrend of studies internationally for analyzing the potential of food production in cities by exploring the implications for land use policies and programs, management of natural resources and changes in rural landscapes in a metropolitan area. Bogor District is one of the peri-urban areas of Jakarta Greater Area (Jabodetabek) which is directly affected by its development as one of the world’s mega-city. This impact is marked by land use changes in Bogor District, where the agricultural land (both wet and dry agricultural land) has experienced significant changes within 1989 to 2013, with a total number of built-up area conversion reaching of 47,953 ha (16.04%). This study aims to identify and analyze the potencial of peri-urban agriculture in Bogor District using remote sensing, geographycal information system and analytical hierarchy process. The main recommendations of this study is the development of multifunctional agriculture that prioritizes of environmental protection development ( eco-friendly agriculture ) with the strategy of development through economic and social aspects. Keywords: Bogor District, Jabodetabek area, multifunction agriculture, peri-urban agriculture